ANALISIS FORMULASI KEBIJAKAN MASA BERLAKU PASPOR 10 TAHUN DALAM PERSPEKTIF KEIMIGRASIAN - Edwinarta, Caesar Demas; Fauzia, Marliana Eka; Agustine, Adhinda Dewi (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
This research is a study of the policy planning for a passport validity period of 10 years by Government Regulation Number 51 of 2020. The regulation explains that the validity period of a passport will be extended to a maximum of 10 years from before. The existence of this will directly change the initial changes and even include the possibility of changing Law Number 6 of 2011 concerning Immigration. Changes to the regulations governing procedures and other matters relating to passports will result in policies that require proper policy formulation. This study uses a qualitative method and is combined with a case study approach which aims to analyze the policy plan for a 10-year passport validity period from an Immigration perspective. The results of the study described that there were positive and negative values to the planned formulation of a 10-year passport validity policy, especially in the aspect of passport abuse problem, citizenship issues and state revenues. The results of this analysis are expected to be able to become a literature study in the plan to formulate a 10-year passport validity policy that will be applied in the future.